Meningkatkan Kemampuan Bercerita Anak melalui Media Buku Cerita Gambar - Martika Hariyani; Dewi Camelia; Yulina Fadilah; Agustiarini Eka Dheasari (AS-SABIQUN, 2022)
From the observations, it is known that the ability of the Qur'ani 'Aisyiyah 1 Play Group children in telling stories is still lacking, which causes them to be less active in the aspect of answering correctly when asked, and retelling what they have heard. There are several things that cause children to lack the ability to tell stories, one of which is less interesting media so that children feel bored. Therefore, a research was conducted by applying picture storybook media to improve the storytelling ability of group B children. The purpose of this study was to see the activities of teachers and children and increase children's storytelling abilities. in this study the researcher used the Classroom Action Research CAR research method. The subjects of this study were group B children in KB Qur'ani 'Aisyiyah 1 Probolinggo city, totaling 7 children with 5 girls and 2 boys with the object of research being the application of picture storybook media in improving children's storytelling skills. The results of the study indicate that picture storybook media can increase teacher activities, children's activities, and improve children's storytelling abilities. Based on the results of the study, it can be concluded that picture storybook media can improve children's storytelling abilities.